Peranan Kelompok Tani Kenongo Mukti terhadap Peningkatan Pendapatan Usahatani Padi Sawah - Bayhaqi Syah, A.; Aden Hawa, Tidar (KUBIS, 2022)
Land area which greatly influences the quantity of production results. With notes, farmers can manage their farms well. Farmers also need knowledge about the farms they manage, in order to increase the quantity of production. One way is that farmers can join and actively participate in activities in farmer groups. This study aims to determine the role of farmer group activities and business units in increasing the income of member farmers. The research site is the Kenongo Mukti Farmer Group, which is located in Kajarharjo Village, Kalibaru District, Banyuwangi Regency. This research uses descriptive analysis method. The sampling method in this study using purposive sampling technique. The results showed that the Kenongo Mukti farmer group had several group activities, including (1) Agricultural Extension, (2) Training, (3) Agro Learning, (4) GP-PTT, (5) Partnership or Cooperation, (6) Meeting Routine, and (7) Capital. The group business units include (1) UPJA, (2) Distribution of Prodi, and (3) Marketing of Production Products. Farmers consider that group activities and business units have a supportive role in increasing the income of their members. It is hoped that the Kenongo Mukti Farmer Group will continue to be consistent in carrying out its vision and mission. And it can be used as an example by other farmer groups, so that it can help the community, especially farmers, to be more prosperous.